The Role of Patient Experience in the Value Assessment of Complex Technologies – Do HTA Bodies Need to Reconsider How Value is Assessed?. Issue 5 (May 2021) - Sarri, Grammati; Freitag, Andreas; Szegvari, Boglarka; Mountian, Irina; Brixner, Diana; Bertelsen, Neil; Kaló, Zoltán; Upadhyaya, Sheela
Highlights: The value of patient experience is becoming increasingly recognized by healthcare stakeholders. Integration of patient experience in health technology assessment is not universally adopted. This is challenging when assessing complex health technologies and holistic solutions. New value frameworks can formalize the patient perspective into complex technology assessments. This paper searched for and summarized current patient experience value frameworks.